“HEAL together”: a randomized, hybrid type 1 effectiveness-implementation trial protocol of a peer-delivered behavioral activation intervention to improve methadone treatment retention - Magidson, Jessica F.; Bradley, Valerie D.; Anane, Jessica S.; Kleinman, Mary B.; Felton, Julia W.; Hines, Abigail C.; Baskar, Rithika; Greenblatt, Aaron D.; Dean, Dwayne; Anvari, Morgan S.; Fitzsimons, Heather; Bennett, Melanie E.; et al. (Frontiers in Public Health, 2025)
BackgroundAlthough medications exist to effectively treat opioid use disorder (OUD), treatment retention is a pressing challenge. Peer recovery specialists (PRSs) may play an important role in OUD treatment retention, yet few evidence-based interventions to support OUD retention have been developed specifically for PRS delivery. Behavioral activation is a brief, reinforcement-based intervention with empirical support for improving depression and substance use outcomes, delivered typically by specialist mental health providers. Informed by key stakeholder feedback, our team adapted a behavioral activation and problem-solving intervention for PRS delivery (“Peer Activate”) to improve methadone treatment retention. Building on a successful open-label pilot trial demonstrating initial feasibility, acceptability, and preliminary effectiveness of Peer Activate, the current type 1 hybrid randomized controlled trial evaluates the effectiveness of Peer Activate compared to treatment as usual on six-month methadone retention (primary) and longer-term implementation outcomes.MethodsThe trial is being conducted at a large methadone treatment program in Baltimore City, Maryland. We are enrolling 200 patients who recently initiated methadone treatment or are experiencing challenges with methadone adherence in a randomized 1:1 ratio to receive Peer Activate plus treatment as usual (PA + TAU) or TAU only. Additionally, we are recruiting 12 stakeholders to provide feedback on implementation and sustainability. Peer Activate consists of four core intervention sessions delivered by a PRS with relevant lived experience and training in the intervention. Sessions focus on problem-solving barriers to retention and behavioral activation—increasing value-driven, substance-free activities—and continued skill practice and relapse prevention. Assessments are administered at baseline, post-treatment (approximately 3 months), and 6 months. The primary effectiveness outcome is methadone retention over 6 months, measured using chart review. Implementation outcomes are defined based on Proctor’s model, including feasibility, acceptability, and fidelity of the intervention.DiscussionThis trial will provide insight as to whether a PRS-delivered intervention may be effective and feasible for improving methadone treatment retention and other behavioral health outcomes. If findings are promising, Peer Activate may provide a platform on which to incorporate an evidence-based behavioral activation approach into PRS training nationally.Clinical trial registrationNCT05299515.